Genomic Characterization of Radiation-Induced Intracranial Undifferentiated Pleomorphic Sarcoma. (8th March 2021) - Hong, Christopher S.; Partovi, Edwin; Clune, James; Huttner, Anita; Park, Henry S.; Omay, Sacit Bulent
Abstract : Intracranial undifferentiated pleomorphic sarcoma remains a rare pathology within the sarcoma literature that may arise primarily or secondary after radiation therapy. Despite first-line treatment with maximal surgical resection, followed by nonstandardized adjuvant chemotherapy/radiation regimens, clinical prognosis remains exceedingly poor. Furthermore, there is a lack of genetic or molecular characterization to guide potential for targeted therapies. We present genomic analysis of a radiation-induced intracranial undifferentiated pleomorphic sarcoma in an 83-year-old woman with notable KIT and PDGFRA alterations. Further similar genomic studies of intracranial pleomorphic sarcoma are needed to develop better therapies for this rare but challenging disease entity.